Congenital toxoplasmosis and audiological outcome: from a case series to a suggestion of patient-based schedule - Salomè, S.; Malesci, R.; Delle Cave, V.; Amitrano, A.; Gammella, R.; Fanelli, F.; Capone, E.; Capasso, L.; Fetoni, A. R.; Raimondi, F. (Frontiers in Pediatrics, 2024)
Introduction. Sensorineural hearing loss (SNHL) has been suggested to be possibly related to congenital toxoplasmosis (CT) although its prevalence varies from 0% to 26%. This variance appears to be dependent especially on early timing of treatment. However, the available data are based on outdated studies conducted on small groups of patients which lack homogeneity. Therefore, in order to establish evidence-based guidelines for audiologic monitoring in CT, we conducted a comprehensive evaluation of a large case series over a long period of time. Patients and Methods. This is a single-center, retrospective cohort which enrolled all infants and children who were exposed in utero to Toxoplasma Gondii and/or congenitally infected from September 1980 to December 2022. They underwent standard serial audiological evaluations to detect possible SNHL at an early stage. The first evaluation was performed during the initial assessment to define the onset of congenital toxoplasmosis, with another evaluation conducted at least at the 12 months of life. Results. We collected data from 1,712 patients and 183 (10.7%) were diagnosed with CT. Among these cases, 78 children (42.6%) presented with symptomatic CT at onset, exhibiting ocular findings (21.1%), clinical cerebral manifestations (6.1%) and/or abnormal finding on neuroimaging (35.5%). Therapy was administrated at onset in 164 patients (89.6%) with 115 of them starting treatment prior to 2.5 months of age (0-388, median 32.00±92.352 days of life). Only 1 patient presented with SNHL at onset, but this was apparently unrelated to CT. The median number of audiological assessments was 2.2±1.543 (2-10). No patients developed any grade of delayed hearing loss, both in treated and untreated groups. The median age at last audiological evaluation was 2.3±2.18 years (1-8) although the median follow-up period was of 12.4 years (±6.3), ranging from 1 to 27 years. Conclusions. Based on these data, it appears that SNHL may be less frequent in CT than previously assumed. We recommend conducting an audiological assessment at onset (within the first 2.5 months of life) to comprehensively define the type of CT onset, and then conducting another evaluation within 9 months of life.